Off-on fluorescent switching of boron-doped carbon quantum dots for ultrasensitive sensing of catechol and glutathione. (June 2020) - Ma, Y.; Chen, A.Y.; Huang, Y.Y.; He, X.; Xie, X.F.; He, B.; Yang, J.H.; Wang, X.Y.
Abstract: A signal-off-on probe of B-doped carbon quantum dot (B-CQD) is developed for ultrasensitive detection of catechol (CC) by fluorescence quenching and glutathione (GSH) by fluorescence recovering without any auxiliary of biomolecules or labeled materials. In this sensing system, the B-CQDs with a high quantum yield of 42% are prepared via a facile hydrothermal method with precursors of citric acid as C source and sodium tetraphenylborate as B source. The microstructure and fluorescence stability of the B-CQDs are investigated. Under the optimum conditions, the B-CQDs are highly sensitive for detecting CC with a linear range of 1–50 nM and a detection limit of 0.25 nM under a typical signal-to-noise ratio of 3 to 1 (S/N = 3), and for sensing GSH with a linear range of 2–100 nM and a detection limit of 0.5 nM (S/N = 3). Meanwhile, the developed B-CQDs show a good selectivity for sensing CC and GSH under high concentrations of interfering substances, such as biological thiols and amino acids. The B-CQDs are successfully applied to determination of CC in river water and GSH in human serum, where the recoveries are 103.3%–106.0% and 99.8%–106.3% for CC and GSH sensing, respectively. The signal-off-on mechanisms of the B-CQDs sensor are discussed. Graphical abstract: Image 1 Highlights: B-doping carbon quantum dots (B-CQDs) was produced. The effects of precursors and hydrothermal reaction on B-CQDs are studied. B-CQDs can detect catechol and glutathione by signal-off-on method. An ultrasensitive detection limit and a good linear range are obtained. The signal-off-on mechanisms of the B-CQDs sensor are discussed.